Amplification Effect of Ground Motion in Offshore Meandering Sedimentary Valley - Hailiang Wang; Shaomin Yan; Zhongxian Liu; Xinglei Cheng (Shock and Vibration)
A sedimentary valley has a visible amplification effect on a seismic response, and the current 2D topographies cannot truthfully reflect the twists and turns of a large-scale river valley. Taking a sinusoidal curved valley site as a model, the dynamic finite element analysis method and the introduction of a viscoelastic artificial boundary were developed to study the 3D seismic response of the dimensional topographies in the homogeneous curved valley to vertical incident P, SV, and SH waves. The results showed that the bending sedimentary valley site earthquake presented significant features simultaneously, depending on the number of valley bends, the frequency of the excitations, the shear wave velocity of sedimentary soil, and the depth of the river valley. The surface displacement amplitudes of three-dimensional meandering sedimentary valleys are significantly different from those of sedimentary basins. The amplification area of the meandering valley is related to the angle between the valley axis and wave vibration direction, and the amplification effect is significant when the angle is small. The movement in the main direction showed a center focus, and the secondary y-direction displacement showed both a central focus and an edge effect. When the frequency of the incident wave was close to the natural vibration frequency in a specific direction, the movement in this direction significantly increased because of the resonance effect. The displacement amplitude of the surface was proportional to the depth of the river valley, and the surface displacement was presented in different forms based on the frequency of the excitations. The results provided some guidance for the earthquake resistance of the curved valley site.